Spiritual meaning and the prophetic mode in T.S. Eliot’s Four quartets - Von Bergen, Megan Kimberly (Kansas State University, 2010)
Among the body of criticism on T.S. Eliot’s Four Quartets, critics such as Cleo McNelly Kearns and Alireza Farahbakhsh have recently interpreted the poet’s “intolerable wrestle / With words and meanings” (EC II) in light of deconstructionist theory. Although the poetry does recognize the difficulty of speaking about spiritual experience, it does not embrace the resulting linguistic miscommunication. In fact, the poems resist such a move, identifying the spiritual danger of such miscommunication; instead, they seek to overcome these difficulties and accurately communicate spiritual experience – an aim achieved in the context of biblical prophecy. Louis Martz argues that the Quartets are, in fact, not prophetic; however, he defines prophecy in terms of its social interests, rather than in terms of the interest in the human-divine relationship that characterizes both biblical tradition and Eliot’s poetry. I want to argue that reading the Quartets in the context of biblical prophecy, filtered through mystical tradition, explains their ability to transcend linguistic difficulty and explore spiritual experience in human language. In biblical tradition, the prophets overcome linguistic difficulty through a direct encounter with God, which purifies language of error and equips them to speak of divine reality. In Eliot’s Quartets, the poetry undergoes a similar purifying experience meant to replace linguistic error with a meaningful exploration of spiritual experience. For the Quartets, linguistic purification is accomplished by means of the mystical via negativa. Appropriating images associated with the via negativa, the poetry denies language tied to direct perception of spiritual reality and adopts instead a language that conveys such experience through unfamiliar words and images. In that language, the poetry is purified of its errors and made capable of exploring the human relationship with God. A poetry identified with the Incarnation, this solution communicates in human language the reality of spiritual experience. In this communication, the poetry at last explores spiritual experience in a way freed of miscommunication and meaningful for the audience, thereby fulfilling its prophetic aims.
Keywords: T.S. Eliot; Four Quartets; Prophecy; Incarnation; Mysticism; Deconstructionist theory; Literature, American (0591); Literature, English (0593); Literature, Modern (0298)